Analisis Pengaruh Video Animasi Lagu Anak Indonesia Terhadap Perkembangan Kosakata Pada Balita Berdasarkan Komponen Linguistik (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
This research explores the potential of Indonesian animated children's songs videos in supporting vocabulary development in toddlers. Sampling from the "Lagu Anak Indonesia Balita" channel on YouTube, the study utilizes observational methods of visual style and literature review to understand children's visual responses to the content. The results indicate that Indonesian animated children's song videos, with their short duration and repetitive lyrics, can create an enjoyable learning experience. From a phonological perspective, the repetition of sounds in the lyrics aids in the recognition of language sounds. Semantic aspects are represented through the introduction of various vocabulary in an easily digestible manner. The simple syntax of the lyrics supports the understanding of basic sentence structures, and pragmatically, these songs can be applied in everyday communicative contexts. In conclusion, Indonesian animated children's song videos can positively contribute to the vocabulary development of toddlers through a holistic and enjoyable approach. The findings of this research can serve as a foundation for the development of early childhood education curricula that effectively utilize animated media.